2004
DOI: 10.1590/s1516-35982004000600012
|View full text |Cite
|
Sign up to set email alerts
|

Exigência de arginina digestível para frangos de corte machos em diferentes fases

Abstract: Três ensaios foram realizados com o objetivo de determinar a exigência de arginina digestível e a relação arginina:lisina digestível para frangos, machos, Avian Farm nas fases de 1 a 20, de 24 a 38 e de 44 a 56 dias de idade. Os experimentos foram conduzidos em delineamento inteiramente casualizado com cinco níveis de arginina digestível, seis repetições e 20 aves por boxe nas fases de 1 a 20 e de 24 a 38 dias de idade e 16 aves por boxe na fase de 44 a 56 dias de idade. Os níveis de arginina digestível utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
5
1
1
Order By: Relevance
“…Corzo & Kidd (2003) recommended even lower levels, 1.15% for live weight gain and 1.28% for feed conversion at the 1 to 18-day age; however, the live weight gain of the birds was very low, around 50% the value obtained in the present result. Atencio et al (2004) did not observe any effect on feed intake; nevertheless, the live weight gain and feed conversion varied quadratically with digestible Arg levels between 1.10 and 1.39% in the 1 to 21-day period.…”
Section: Discussionmentioning
confidence: 60%
“…Corzo & Kidd (2003) recommended even lower levels, 1.15% for live weight gain and 1.28% for feed conversion at the 1 to 18-day age; however, the live weight gain of the birds was very low, around 50% the value obtained in the present result. Atencio et al (2004) did not observe any effect on feed intake; nevertheless, the live weight gain and feed conversion varied quadratically with digestible Arg levels between 1.10 and 1.39% in the 1 to 21-day period.…”
Section: Discussionmentioning
confidence: 60%
“…In studies with broilers (Costa et al 2001;Atencio et al, 2004) found no influence of arginine levels on the performance of growing birds. However, Brake et al (1998), also working with broilers, observed improved feed conversion linearly with increasing the arginine/lysine ratio Table 4 -Arginine/lysine ratio in the diet on the parameters of egg quality from 1.05 to 1.49 in the diet, at a temperature of 31 ºC; this result indicates that high temperatures require high ratios of arginine/lysine in the diet.…”
Section: Resultsmentioning
confidence: 96%
“…The use of methionine, L-lysine and L-threonine in broiler feed is well established, while other amino acids as tryptophan and arginine are generally considered as the next limiting amino acids in broiler feed. The arginine (Arg) is a 'next limiting' amino acid due its antagonism with lysine (Lys) and if Lys was added to a diet, also the requirements of Arg increases (Jones et al 1967;Austic & Scott 1975) and this can affect broiler performance (Balnave & Barke 2002;Atencio et al 2004) and muscle development (Fernandes et al 2009). Tryptophan, apart from being a structural component of all protein is a precursor of serotonin and melatonin, regulating the broiler circadian rhythm and thus feed intake and growth (Emadi et al 2011).…”
Section: Introductionmentioning
confidence: 99%